Optimalisasi Administrasi dan Pengawasan Layanan Pajak Daerah di Kabupaten Nabire Melalui Aplikasi Web - Aprilia Anes Sarira; Gunawan Prayitno (STMIK Pesat Nabire, 2025)
The Land and Building Tax (PBB) and the Duty on the Acquisition of Land and Building Rights (BPHTB) serve as crucial fiscal tools for enhancing regional financial independence. In Nabire Regency, administrative and monitoring processes for both taxes are still managed manually, resulting in inefficient service flow, operational delays, and data integrity issues. This study presents the design and development of an internal web-based information system aimed at supporting more structured and accountable tax service management. The system was created using the Waterfall model, encompassing sequential stages: needs analysis, design, implementation, testing, and maintenance. The results demonstrate that the application facilitates faster taxpayer data retrieval, enables real-time tracking of service progress, and delivers well-organized tax arrears data. Its deployment in Nabire’s Regional Revenue Agency (Bapenda) has contributed significantly to improving staff productivity, data reliability, and public trust. These outcomes lay a groundwork for advancing digital transformation in public services, especially in regions still dependent on manual workflows